Synthesis and Biological Evaluation of S-Substituted Perhalo-2-nitrobuta-1,3-dienes as Novel Xanthine Oxidase, Tyrosinase, Elastase, and Neuraminidase Inhibitors - Nihal Onul; Onur Ertik; Neşe Mermer; Refiye Yanardag (Journal of Chemistry)
S-substituted perhalo-2-nitrobuta-1,3-dienes 3a, b were synthesized by the reaction of polyhalo-2-nitrobuta-1,3-dienes 1a, b with allyl mercaptan. 1-(2,3-Dibromopropanethio)-4-bromo-1,3,4-trichloro-2-nitrobuta-1,3-diene 4 was obtained from the addition of bromine to S-substituted polyhalo-2-nitrobuta-1,3-diene 3b in carbon tetrachloride. Sulfoxides 5a, b, and 6 were obtained from the reaction of thiosubstituted polyhalonitrobutadienes 3a, b, and 4 with m-CPBA in CHCl3. The structures of the new compounds were determined by spectroscopic data (FTIR, 1H NMR, 13C NMR, MS). These compounds exhibited antixanthine oxidase, antityrosinase, antielastase, and antineuraminidase activities.